2013
DOI: 10.1159/000355064
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Importance of a Fixed Bowel Loop in the Treatment of Necrotizing Enterocolitis

Abstract: Background: The need for surgical treatment in neonates with necrotizing enterocolitis (NEC) is associated with high mortality. Although pneumoperitoneum and progressive disease are generally accepted indications for surgery, it is unclear whether a fixed bowel loop (FBL) should prompt surgery. Objective: To determine the relationship between an FBL, type of treatment, and death in the management of NEC. Methods: Retrospective analysis (January 2000-December 2011) of all neonates with definite NEC in a tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…The distribution of opinions on persistent loop on sequential radiographs and portal venous gas on AR as indications for surgery is similar to the equivocal results in the literature [ 30 32 , 37 41 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The distribution of opinions on persistent loop on sequential radiographs and portal venous gas on AR as indications for surgery is similar to the equivocal results in the literature [ 30 32 , 37 41 ].…”
Section: Discussionsupporting
confidence: 77%
“…Fotter and Sorantin suggested that radiographic and ultrasonographic indications should be “free intraperitoneal gas, free intraperitoneal fluid, and diminished bowel gas with asymmetric loops and persistent dilated loops on at least two follow-up studies” [ 24 ]. Of these, only PP on AR is generally accepted [ 34 , 35 ], but, because of its low sensitivity [ 9 , 13 , 36 ], other signs, such as a persistent/fixed loop are still under discussion [ 30 32 , 37 , 38 ]. PVG on AR has been associated with poor outcome and need for surgery [ 37 40 ], mediated by the severity of NEC [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of articles may, however, not be complete. 40 1976 X Daneman 22 1978 X X X X X X Kogutt 41 1979 X Mata 48 1980 X X X Leonard 73 1982 X *Cikrit 74 1985 X Frey 75 1987 X X *Kennedy 76 1987 X Kosloske 56 1988 X X X Brill 77 1990 X Bömelburg 78 1992 X X X Rehan 43 1999 X X X X X X Molik 57 2001 X Tam 31 2002 X X X Faingold 70 2005 X Kim 60 2005 X Sharma 23 2005 X X X Coursey 50 2009 X X X X X X X Dördelman 24 2009 X X Bonhorst 34 2011 X Dilli 61 2011 X X X X Muchantef 53 2013 X X X X X X Silva 72 2013 X X X X Muller 79 2014 X * Abstracts only accessed US has been suggested to be used for: detection of PI, PVG, and intra-abdominal fluid and evaluation of bowel peristalsis, thickness, and perfusion of the bowel wall in neonates with mild symptoms and nonspecific plain film findings;…”
Section: Pathophysiologymentioning
confidence: 99%
“…31,37,75 Other signs, such as persistent/fixed loop and PVG are discussed. 23,46,56,57,59,79,204 Although PVG on AR has been associated with poor outcome, 56 it has also been suggested that not PVG, but severity of NEC, is associated with the need for surgical intervention. 23 Ultrasonographic signs that may indicate intestinal necrosis and need for surgery include localized and/or turbid fluid 53,68,72 and absent perfusion with reduced peristalsis.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation